The effects of the dental methacrylates TEGDMA, Bis‐GMA, and UDMA on neutrophils in vitro - Sara Alizadehgharib; Ann‐Karin Östberg; Agnes Dahlstrand Rudin; Ulf Dahlgren; Karin Christenson (Wiley, 2020)
Abstract Objectives The prevalent usage of methacrylates in modern dentistry demands good knowledge of their biological impacts. While there have been several studies demonstrating the effects of different methacrylic monomers on mononuclear white blood cells, very little is known about the effects caused by these monomers on neutrophilic granulocytes. The objective of this study was to add novel knowledge about how neutrophils are affected by exposure to triethylene glycol dimethacrylate (TEGDMA), urethane dimethacrylate (UDMA), and bisphenol A glycol dimethacrylate (Bis‐GMA) alone or in combinations. Materials and Methods Isolated neutrophils were cultured in the presence or absence of methacrylates. The IL‐8 release was measured using a DuoSet ELISA development kit. Apoptosis and necrosis were analyzed using flow cytometry. The formation of neutrophil extracellular traps (NETs) was investigated using Sytox green DNA staining combined with microscopically examination of released DNA and myeloperoxidase (MPO). Results The release of IL‐8 was significantly increased after exposure to TEGDMA, Bis‐GMA, UDMA, or TEGDMA in combination with Bis‐GMA or UDMA compared to the unstimulated controls. Exposure to TEGDMA, UDMA, and Bis‐GMA for 24 hr separately or in combination did not affect apoptosis or necrosis of the exposed neutrophils. NET structures were formed by neutrophils after exposure to the different combinations of the methacrylates. Conclusion The combination of TEGDMA and Bis‐GMA had a synergistic proinflammatory effect on neutrophils by increasing the release of IL‐8 and the formation of NET structures. The changes in the normal functions of neutrophils caused by methacrylate exposure may lead to altered inflammatory response and relate to previously reported adverse immune reactions caused by these substances.